The Prudence of Religious Commitment - Tilley, Terrence W. (Horizons, 1989)
This essay adopts Penelhum's analysis of parity arguments to show that Christian theistic faith and atheistic secular humanism are on an epistemic par with each other. It argues that Swinburne's attempt to show that theism is more probable than atheism fails because his ultimate canon of rationality is essentially contested and cannot render theism more probable than atheism. It proposes a way out of the epistemic stalemate by evaluating the prudence of religious commitment. It adapts some of Mavrodes' recent arguments and Swinburne's levels of rationality to analyze the dimensions of prudence. It finally extends this "prudential calculus" to indicate how a theologian could show a religious commitment prudent, and argues that if religious authorities silence theologians, the authorities may also show that commitment to and in their tradition cannot be comprehensively prudent.